Addressing opioid misuse and mental health conditions through interdisciplinary workforce development programs. Issue 3 (4th May 2021) - Weller, Bridget E.; Carver, Joshua N.; Harrison, Jennifer; Chapleau, Ann
ABSTRACT: The purpose of this article is to describe two innovative, interdisciplinary workforce development programs that aim to meet the needs of individuals who misuse opioids and may contend with mental health conditions in historically underserved communities. The article begins by highlighting the need for interdisciplinary workforce development programs for social work and occupational therapy graduate students as well as for peer support workers and community providers. Next, a detailed description of two federally-funded training programs is provided. The article concludes with recommendations for workforce development programs.